Knowledge, Attitude and Practices related to AI among poultry workers of Bangladesh - Hossain, Sarder Mahmud; Eusufzai, Sumaiya Zabin; Elahi, Mustafa Mahbub; Jamayet, Nafij Bin (Bangladesh Journal of Medical Science, 2015)
Background: AI (Avian influenza) refers to a large group of different influenza viruses that primarily affect birds. On rare occasions, these bird viruses can infect other species, including pigs and humans. The vast majority of avian influenza viruses do not infect humans. Objective: To assess knowledge, attitude and practices related to AI among poultry workers. Methodology: A descriptive cross sectional study was designed to conduct in Bangladesh with a pretested modified questionnaire by face to face interview. Result: Current study revealed that nearly one third of the respondents were belonged to age group 26-30 years (39.17%) with the mean age 32.18±6.65 years. Majority of the respondents were male (70%). Nearly two thirds (80%) were owners of poultry farms. Half of them (49.67%) got information regarding AI by electronic media. Nearly one third of the study respondents (34.17%) replied that hand washing after poultry care and less than one third of the respondents (31.67%) said by using PPE (Personal Protective Equipment) during poultry care can prevent AI. Most of the participant said that they informed Rapid Response Team (RRT) for management of sick or dead poultry. More than half of the respondents (57.5) were using PPE. Association found between Socio-demographic variable (Age) and Knowledge on preventing avian influenza among the respondents where p-value=0.001. Conclusion: Knowledge and practices about AI disease among the poultry workers was moderate, but their attitudes were positive. Therefore, designing and implementing health educational programs and ensure proper training for poultry workers about AI to improve preventive practices should have the priority to eliminate the disease. DOI: http://dx.doi.org/10.3329/bjms.v14i1.21558 Bangladesh Journal of Medical Science Vol.14(1) 2015 p.26-31